Extraneous doping and its necessary preconditions - Sojka, Antonín; Janíček, Petr; Zich, Jan; Navrátil, Jiří; Ruleová, Pavlína; Plecháček, Tomáš; Kucek, Vladimír; Knížek, Karel; Drašar, Čestmír (Elsevier Science BV, 2024)
Modulation doping in semiconductors has attracted much interest because of its ability to provide a reasonable concentration of free carriers without compromising their mobility, which is significantly reduced by conventional doping. It is very rare to find structures such as Bi2O2Se, which can be thought of as having a separate ""doping part"" (Se) and ""conducting part"" (Bi2O2). Such a structure allows a high carrier mobility at reasonable carrier concentrations. These structures can be viewed as natural electronic composites and this process is often referred to as modulation or delta doping. In this study, we explore and discuss the possibilities of similar but artificial electronic composites - materials doped due to the presence of a foreign phase. Although, such a doping is probably almost ubiquitous in heterogeneous systems, it is very unlikely to provide a reasonably high and homogeneous concentration (10^(18) cm^(-3)) of free charge carriers. Rather, the foreign phase often merely modifies the stoichiometry of the matrix and thus the concentration of native point defects and hence free charge carriers. However, our study shows that although the chance of achieving effective modulation doping is small for 3D structures, it increases significantly for both 1D and 2D structures for low-volume nanoinclusions (<10 nm^(3)). This work also provides guidance on the proper choice of material pairs with respect to modulation doping.
Vnější doping a jeho nezbytné předpoklady
Keywords: Electrical properties; Charge transfer; Finite element modeling; Composite; Materials with reduced dimensions; Elektrické vlastnosti; Přenos náboje; Modelování konečných prvků; Kompozity; nízkodimenzionální materiály